Water safety screening via multiplex LAMP-Au-nanoprobe integrated approach - Oliveira, Beatriz B.; Veigas, Bruno; Carlos, Fábio Ferreira; Sánchez-Melsió, Alexandre; Balcázar, José Luís; Borrego, Carles M.; Baptista, Pedro Viana (The Science of the total environment, 2020)
Contaminated water resources remain a major global concern regarding public health. The majority of water safety protocols include indicators of microbial contamination to evaluate the potential risk to public health and are key elements of quality guidelines. Among these, markers for total coliforms and fecal coliforms are strong indicators of co-contamination with other pathogens. Traditional methods, recurring to slow and cumbersome culture-based approaches, have been gradually replaced by molecular methods, capable of faster and more specific screening. These are usually PCR-based methods that may allow for multiple pathogen detection but require dedicated laboratory equipment, hindering the rapid on-site assessment. Here, we used a multiplex Loop-Mediated Isothermal Amplification (mLAMP) strategy for the amplification of two markers associated with the contamination by total and fecal coliforms (e.g. Escherichia coli) — lacZ and uidA genes, respectively — thus allowing for single tube multiplex detection. The mLAMP products were then subject to an Au-nanoprobe colorimetric detection assay for precise discrimination of targets. This approach was validated in 22 water samples that were also screened for the presence of lacZ and uidA using standard and quantitative PCR, with the capability for discriminating the contamination level, e.g. a semi-quantitative evaluation of water quality. [Display omitted] •Multiplex LAMP (mLAMP) coupled to colorimetric Au-nanoprobe assay for microbial contamination.•mLAMP allows for fast detection of presence of critical genes of contamination.•Au-nanoprobe coupled to mLAMP allows for precise discrimination of molecular targets.•mLAMP+Au-nanoprobe suitable for assessing contamination level (semi-quantitative assay).